Suolistomikrobiston ja kehonkoostumuksen yhteydet fitness- ja kehonrakennuslajien kilpailijoilla - Lappalainen, Roosa (2025)
Lappalainen, R. 2025. Associations of gut microbiota composition and body composition on competitive fitness- and body building athletes. Faculty of Sport and Health Sciences, Uni-versity of Jyväskylä, Master’s thesis, 74 pp..